Upaya Meningkatkan Keterampilan Kerja Sama Peserta Didik Melalui Penerapan Model Problem Based Learning (PBL) Kelas IV Di SDN 16 Mataram Tahun Pelajaran 2022/2023 - Yeni Rostiana; Deni Tri Agus Mahardikha; Siti Istiningsih (Journal of Science Instruction and Technology, 2023)
This study was motivated by students' poor collaboration skills during learning implementation. The objective of this training is to attempt to improve collaboration skills through the application of Problem Based Learning (PBL) model in Class IV in SDN 16 Mataram. This type of research is called collaborative classroom inquiry (PTKK). The data collection methods used in this study are observation, questionnaire and documentation. The subjects of the study were 30 students of class IV SDN 16 Mataram. The results of the study show that the application of problem-based learning (PBL) model can improve students' collaboration skills and improve learning outcomes of SDN 16 Mataram Class IV students. The results of the study showed that in Cycle I, the percentage of students who achieved the goal for collaboration skills was 56%, and in Cycle II increased to 79%. And according to the results of the first cycle, the percentage of students who completed the completion plan, namely 70%, increased to 85% in the second cycle. The conclusion of this study is that through the application of Problem-Based Learning (PBL) model, collaboration skills can be improved in Class IV SDN 16 Mataram in the academic year 2022/2023.